A Retrospective. A few Reflections on My Own Eightieth Birthday - Loewenstein, Bedřich (Dějiny – teorie – kritika, 2009)
In this autobiographical contribution, the author contemplates the development of his own thinking and research. He presents it as a public confession on the topic of repeated falls and failures and the will to begin again. Th is document of self-history thus, using the author’s own story, also provides insight into the intellectual history of the twentieth century.